The Effect Of Problem Based Learning Model On Students Outcomes In Learning Natural Science Of 5th Grade At UPT SDN 104 Tontonan Anggeraja District Enrekang Regency - Nurhaedah Nurhaedah; Hartoto Hartoto; Nur Ilmi Amalia (Program Studi PGSD FIP UNM, 2022)
This research discusses the effect of the application of the problem based learning model on the science learning outcomes of fifth grade students of UPT SDN 104 Tontonan. This type of research is an experimental research using the One Group Pretest-Posttest Design research design. The independent variable in this study is a problem based learning model. The dependent variable in this study is the student's natural science learning outcomes. The population used is all students of class V as many as 17 students and using a sampling technique that is saturated sample. Data collection techniques in this study were tests, observations, and documentation. The instrument used in this research is multiple choice questions, totaling 15 questions. Data analysis used descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis showed that the description of the application of the problem based learning model at the first meeting was running effectively and the second meeting was running very effectively. The achievement of learning outcomes shows an increase when using the problem based learning model, this is proven by the posttest average value being higher than the pretest average value. The results of hypothesis testing using Paired Sample t-test showed a significant value less than 0.05 and the results of T Count > T Table, so H0 was rejected and Ha was accepted, which means that the application of the problem based learning model has an effect on the science learning outcomes of 5th grade students at UPT SDN 104 Tontonan, Anggeraja District, Enrekang Regency.